THE EVANGELICAL QUADRILATERAL: A RESPONSE. - Bebbington, David W. (Fides et historia, 2015)
The author responds to comments on his book "Evangelicalism in Modern Britain: A History From the 1730s to the 1980s." He discusses the approach taken by the Baptist Missionary Society to evangelicalism in Serampore, India during the 19th century. He argues that the role of the Holy Spirit in evangelicalism should not be the prominent feature of evangelicalism. The author also affirms that evangelicals have believed that evangelicalism existed.